The effects of nasal lavage with betamethasone cream post-endoscopic sinus surgery: clinical trial. Issue 2 (12th September 2017) - Dawson, B; Gutteridge, I; Cervin, A; Robinson, D
Abstract: Background: Steroid nasal irrigation for chronic rhinosinusitis patients following endoscopic sinus surgery reduces symptom recurrence. There are minimal safety data to recommend this treatment. This study evaluated the safety of betamethasone nasal irrigation by measuring its impact on endogenous cortisol levels. Methods: Participants performed daily betamethasone nasal irrigation for six weeks. The impact on pre- and post-intervention serum and 24-hour urinary free cortisol was assessed. Efficacy was evaluated using the 22-item Sino-Nasal Outcome Test. Results: Thirty participants completed the study (16 females and 14 males; mean age = 53.9 ± 15.6 years). Serum cortisol levels were unchanged ( p = 0.28). However, 24-hour urinary free cortisol levels decreased (47.5 vs 41.5 nmol per 24 hours; p = 0.025). Sino-Nasal Outcome Test scores improved (41.13 ± 21.94 vs 23.4 ± 18.17; p < 0.001). The minimal clinical important difference was reached in 63 per cent of participants. Conclusion: Daily betamethasone nasal irrigation is an efficacious treatment modality not associated with changes in morning serum cortisol levels. The changes in 24-hour urinary free cortisol levels are considered clinically negligible. Hence, continued use of betamethasone nasal irrigation remains a viable and safe treatment option for chronic rhinosinusitis patients following functional endoscopic sinus surgery.